Money demand under a fixed exchange rate regime: The case of Saudi Arabia - Fakhri J. Hasanov; Moayad Al Rasasi; Salah S. Alsayaary; Ziyadh Alfawzan (Journal of Applied Economics, 2022)
This paper reviews earlier studies and shows that the money demand (MD) relationship under a fixed exchange rate (ER) regime differs from that under a floating ER regime, mainly due to the limited role of monetary policy in the former regime. It then empirically demonstrates that an open-economy model augmented with country-specific factors is a better framework for characterizing the MD function under a fixed ER regime by applying cointegration and equilibrium correction modeling to the Saudi data as a case study. The main message for monetary authorities is that there are other factors, besides those theoretically predicted, shaping MD under a fixed ER regime. This information is important for providing adequate money supply to support economic growth and maintain the stability of the fixed ER, as well as for checking the stability of the MD to make appropriate policy decisions.
Keywords: 330; autometrics; cointegration; fixed exchange rate; monetary policy; money demand; oil price; Saudi Arabia